Irrationality of Attitudes toward Safety under Complexity and Uncertainty Leading to Asymmetry of Information - Atsuo Murata (MDPI AG, 2021)
This study investigated how complexity and uncertainty, the probability of accidents, and the probability of financial trouble affected individuals’ recognition of validity of irrational risk-seeking decisions. As a result of conducting a multiple regression analysis on the validation score for irrational risk-seeking alternative obtained by a questionnaire survey, we found that the validity score for an irrational risk-seeking alternative was higher when both complexity and uncertainty were high than when both complexity and uncertainty were low, which means that high complexity and high uncertainty in the situation of decision making more readily leads to an irrational risk-seeking behavior that might trigger a major accident. Beyond complexity and uncertainty, the damage of major accident α, the decrease of the probability of major accidents and the increase of the probability of financial trouble (economic factor) were also found to promote the choice of irrational risk-seeking alternatives. Some implications for safety management under high complexity and uncertainty are discussed.